Can The Customer Value Proposition Form Customer Loyalty? - Zainal Abidin; Tetra Hidayati; Suharno Suharno (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2022)
The aim of this study was to analyze and study the effect of customer proposition value on customer loyalty for heavy equipment products in Kalimantan with customer satisfaction as a mediating variable and customer profile as a moderating variable. This type of research is explanatory research using a questionnaire as a data collection tool. The population of this research is heavy equipment user companies in Kalimantan, with a sample size of 100 companies. Data were analyzed using structural equation modeling. The research findings reveal that the customer proposition value has a significant effect on customer loyalty and customer satisfaction is meaningful as a mediating variable, meaning that the increase in customer perception of the customer value proposition is unidirectional and significant towards increasing company customer loyalty using heavy equipment products. Customer profile has a positive meaning to strengthen customer value proposition towards customer loyalty. The practical implication of this study is to provide an understanding that the customer value proposition that matches customer expectations is one of the important concepts to increase customer loyalty and customer profile to strengthen relationships.